The Correlation Analysis between Bullying and Experiences in Close Relationships in High School Students - Aslan, Sevda (International Journal of Humanities and Social Science Research, 2015)
In this study, it is aimed to determine whether there is correlation between the school bullying and the experiences of adolescents in their close relationships. The participants of this study consisted of children from 9th,10th,11th,12th grades of three different high schools. In this research, Student Relationships Attitude Scale and Experiences in Close Relationships Inventory were used as data collection tools. Results of the study revealed significant positive relationships between the bullying personality attitude and attachment avoidance and attachment worry dimensions of the Experiences in Close Relationships Inventory. Significant relationships were found between confident attitude and attachment avoidance dimension of the Experiences in Close Relationships Inventory.